The Oxford handbook of the Dead Sea Scrolls - Lim, Timothy 1960- (Oxford [u.a.] Oxford University Press, 2010)
30 international scholars probe the main disputed issues in the study of the Dead Sea Scrolls. Essays engage with the lively debate continues over the archaeology and history of the site the nature and identity of the sect, and its relation to the broader world of Second Temple Judaism and to later Jewish and Christian tradition.
Reproduktion
Keywords: Dead Sea Scrolls -- Criticism, interpretation, etc; Dead Sea scrolls ; Criticism, interpretation, etc; Dead Sea scrolls; Aufsatzsammlung